Biblical Knowing: A Scriptural Epistemology of Error. By Dru Johnson - Keefer, Arthur (The journal of theological studies, 2014)
Scholars have renewed an interest in blending the disciplines of philosophy and theology. Dru Johnson contributes to this endeavour by bridging Scripture and epistemology, examining the Bible’s perspective on what and how we know. He claims to ‘lay the groundwork for a biblical theology of knowledge’ (p. xv). In response to philosophy’s aged discussion of is and ought, the Bible provides a descriptive and prescriptive epistemology: ‘the way knowing is supposed to work and how it actually works’ (p. xxi)., In his first chapter Johnson defines faith and error and establishes a method for reading the Old and New Testaments. Faith, rather than a blind commitment, is attentively listening to authoritative guides, embodying their instructions, and looking at what they show the learner.